La geste des gestes (extrait) - Pascal Krajewski (Appareil)
Gestures are genuine “stress marks” on a society: they forge the expressivity of its body. Every gesture means and needs a technè, a know-how; and most of them are the counterpart of an existing tool. The industrial and technological shifts have introduced new kinds of objects, and thus, they have changed our gestural vocabulary and its use.